Semisupervised learning of author‐specific emotions in micro‐blogs. Issue 6 (1st September 2016) - Kang, Xin; Ren, Fuji; Wu, Yunong
Abstract : Learning emotions from texts has been an active research topic in affective computing. However, the lack of reliable connection between emotions and language features has caused severely biased emotion predictions. Moreover, the author‐specific patterns in emotion expression could potentially affect emotion predictions, which has never been studied. In this paper, we propose a semisupervised learning algorithm to learn emotional features from large‐scaled micro‐blog documents with a Bayesian network, and introduce an emotion transition factor to generate the author‐specific emotion predictions. We infer the author‐specific emotions in micro‐blog streams through belief propagation, and learn the emotional features through an expectation maximization estimation procedure. We report results of single‐label and multilabel emotion predictions on a micro‐blog stream corpus, and analyze the improvements achieved by the semisupervised feature learning strategy and the incorporation of emotion transition patterns. Finally, we perform personality analysis based on the authors' emotion distribution and examine emotion distributions in the learned features. © 2016 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.